Application of Lasers in Manufacturing Select Papers from AIMTDR 2016 - Dixit, Uday Shanker; Joshi, Shrikrishna N.; Davim, J. Paulo (Lecture Notes on Multidisciplinary Industrial Engineering,, 2019)
This book mainly addresses the applications of lasers in the manufacture of various industrial components. The technologies presented here have scopes of application ranging from the macro to meso and micro level of components and features. This book includes chapters on the basic and advanced applications of lasers in the manufacturing domain. They present theoretical and practical aspects of laser technology for various applications such as laser-based machining, micro-scribing, texturing, machining of micro-sized channels; laser welding; laser-based correction of sheet metal, i.e. straightening; laser forming; and laser technology for 3-D printing. Lasers have various applications such as the production of powerful lights for illumination or decoration; measurement of velocity (transportation) and length; interferometry; printing; recording; communication; bio-medical instrumentation and pollution detection. A significant body of literature is available on the physics of lasers and types of lasers. However it has been noted there are a few books published on the "applications of lasers in manufacturing domain," a gap that this book remedies. Gathering contributions by leading engineers and academicians in this area, it offers a valuable source of information for young scientists and research students. .